Rights, duties, justice and moral symmetry from a scientific philosophy - Ordóñez González , José Rafael; Teixidó Durán, Óscar Frederic (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2023)
The article presents and discusses, from a materialistic and pluralistic philosophical framework, new concepts of: morality, law, justice, equity, freedoms, legal rights, moral rights, legal duties and moral duties. A series of relevant relationships are established between these ideas through scientifically informed philosophical notions. Then, a proposal of normative justice as equity with symmetrical moral prescriptions is constructed, based on the definitions of properties of social dependencies and freedoms. Finally, applying the developed concepts, international human rights instruments are analyzed from a descriptive and prescriptive perspective.
Keywords: ethics; morals; law; duty; freedoms; social dependencies; justice; rights; equity; HHRR